Religious practices and networks of belonging in an immigrant congregation: the German-speaking Lutheran congregation in Dublin - Ritter, Christian S. (Journal of contemporary religion, 2017)
This article explores how members of the German-speaking Lutheran church in Dublin develop their networks of belonging by taking part in social practices in their congregation. The article addresses the intersection of religious life, migration experience, and belonging. Based on qualitative fieldwork, we assess how social practices embedded in religious activities and beliefs reshape the sense of belonging among members of this congregation. We study the congregation through a material approach while paying attention to its actual religious and social life. The study observes how participation in the social life of the congregation enables its members to create multiple senses of belongingethno-cultural, religious, and social belonging. The social life of the congregation aids the preservation of immigrants' ethno-cultural particularities, societal adaptation, and sense of belonging to their religious community.